Maximization of calcium and phosphate in neonatal total parenteral nutrition. Issue 7 (20th June 2018) - Maruyama, Hidehiko; Saito, Jumpei; Nagai, Miki; Mochizuki, Mai; Ishikawa, Yoichi; Ito, Yushi
Abstract: Background: Appropriate calcium and phosphate supplementation is essential for bone growth in preterm infants. Using Rehabix‐K2™ (AY Pharmaceuticals, Tokyo, Japan) and Pleamin‐P Injection™ (Fuso Pharmaceutical Industries, Osaka, Japan) as the total parenteral nutrition (TPN) and amino acid solution, respectively, we investigated ways of maximizing calcium and phosphate in the TPN solution. Methods: Rehabix‐K2, Pleamin‐P, calcium gluconate, sodium phosphate, 50% glucose, and water were mixed in varying proportions to create 16 formulations. Precipitation assessment was done three times for each of the 16 formulations, and was based on the Japanese Pharmacopeia. Result: Precipitation was observed 24 h after mixing when the calcium and phosphate were 60 mEq/L and 30 mmol/L or 80 mEq/L and 40 mmol/L, respectively. No precipitation was observed when the calcium and phosphate were 20 mEq/L and 10 mmol/L, respectively. Precipitation was observed once out of three times, when the calcium and phosphate were 40 mEq/L and 20 mmol/L, respectively, and the amino acids were 2% and 3% (mean pH, 6.13 and 6.26, respectively). No precipitation was observed, however, when the calcium and phosphate were 40 mEq/L and 20 mmol/L, respectively, and the amino acids were 0% and 1% (mean pH, 5.88 and 6.05, respectively). Conclusion: Not only the concentration of calcium and phosphate, but also the pH of the TPN solution, are crucial factors for precipitation. Based on these results, a well‐balanced TPN solution maximizing calcium and phosphate availability will be able to be formulated.